SeLIMuT Therapy: Self-Selected Individual Music to Reduce Pain in Cancer Patients at Dharmais - Rohana I Gusti Ayu Putu Desy; Febtian Cendradevi Nugroho; Yusniarita Yusniarita; Theresia Avila Kurnia; Ame Ame; Rudi Rudi; Ria Andjarwati; Retno Setiowati (School of Health Sciences Al-Ma'arif, 2025)
Cancer is a disease characterized by abnormal cell growth that invades body tissues, causing pain and discomfort. This pain and discomfort result from tumor pressure on nerves or side effects of treatments such as surgery, chemotherapy, and radiation. This study aims to evaluate the effectiveness of Self-Selected Individual Music Therapy (SeLIMuT) in reducing pain in cancer patients at Dharmais Cancer Hospital. The research method employed is a case study with pre-test and post-test pain level measurements and monitoring responses during each therapy session. The study involved 10 patients experiencing mild to moderate pain. Music therapy was conducted four times over two days, with each session lasting 15 minutes. Music chosen by the patients themselves created distraction and relaxation effects while stimulating endorphin release, contributing to a reduced perception of pain. The results showed that the SeLIMuT intervention was effective and safe, significantly reducing pain levels measured using the Numeric Rating Scale (NRS). In addition to pain relief, music therapy provided emotional comfort and relaxation for the patients. Future studies are recommended to involve a larger sample size, include various cancer types and palliative treatments, and explore different music genres and the psychological impacts of music therapy.